Individual Differences in the Neural and Cognitive Mechanisms of Single Word Reading - Fischer-Baum, Simon; Kook, Jeong Hwan; Lee, Yoseph; Ramos-Nuñez, Aurora; Vannucci, Marina (Frontiers in Human Neuroscience, 2018)
Written language is a human invention that our brains did not evolve for. Yet, most research has focused on finding a single theory of reading, identifying the common set of cognitive and neural processes shared across individuals, neglecting individual differences. In contrast, we investigated variation in single word reading. Using a novel statistical method for analyzing heterogeneity in multi-subject task-based fMRI, we clustered readers based on their brain’s response to written stimuli. Separate behavioral testing and neuroimaging analysis shows that these clusters differed in the role of the sublexical pathway in processing written language, but not in reading skill. Taken together, these results suggest that individuals vary in the cognitive and neural mechanisms involved in word reading. In general, neurocognitive theories need to account not only for what tends to be true of the population, but also the types of variation that exist, even within a neurotypical population.